Peran Teologi Proses dalam Membangun Harmoni Antaragama di Era Modern - Rangga Abednego Simaremare (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research discusses Process Theology as a theological perspective that understands God and the world as aspects of a process that continues to change and develop. In the midst of a diverse and diverse modern society, Process Theology provides an inclusive framework to facilitate positive interfaith dialogue. Through a literature review, this research explains the main principles of Process Theology and how their application can support the creation of harmony and tolerance between various religious groups. This approach emphasizes the importance of respecting diversity and universal values ​​that exist in various religious traditions. The findings of this research indicate that Process Theology can be an effective foundation for reducing divisions due to religion and strengthening solidarity in society. This study contributes to the development of theological thinking that is relevant to the challenges of plurality and diversity in the modern era.